"ELECTRONIC EXPERT" EXPERT SYSTEM SUBSYSTEM'S "DE- SIGN" CONSTRUCTION FEATURES - L.V. BORISOVA (Advanced Engineering Research, 2009)
One of the expert system for maintenance service of combine harvester subsystem's structure will be carried out.